If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -8) * 6 = 30 Reorder the terms: (-8 + n) * 6 = 30 Reorder the terms for easier multiplication: 6(-8 + n) = 30 (-8 * 6 + n * 6) = 30 (-48 + 6n) = 30 Solving -48 + 6n = 30 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 6n = 30 + 48 Combine like terms: -48 + 48 = 0 0 + 6n = 30 + 48 6n = 30 + 48 Combine like terms: 30 + 48 = 78 6n = 78 Divide each side by '6'. n = 13 Simplifying n = 13
| x^2+12x-25=0 | | -2+-2=-2(x-5)-6 | | 77-3x=24x+14 | | 5x+35=14x-36 | | 1+2[3(x-1)-5(2x-3)]=2x-7 | | 4x+5-10x=8+3x+12 | | 5x+31=tx+11 | | 4x^2+7x-8=0 | | 8b-4(b-2)=42 | | -6-20=-2n | | 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 | | 51-81.623= | | 0=(.25x^4)-(2x^2)-1 | | 7.2g+1.5=6+3.2g | | 2x^2+4x-10=0 | | 5x+2(x-3)=12x-5+14 | | 4(2x+3)-6x=18 |